THE EXTRACTION OF BROWN ALGAE (Sargassum sp) THROUGH CALCIUM PATH TO PRODUCE SODIUM ALGINATE (Universitas Negeri Semarang, 2018)
Brown algae is a source of sodium alginat raw material. One type of brown algae that is found to grow in Indonesian waters is Sargassum echinocarphum. Brown algae including one type of seaweed that grows in many waters of Indonesia, especially the waters of Eastern Indonesia. Alginat is a pure polysaccharide of uronic acid contained in a brown algae cell wall arranged in the form of long linear chain alginic acids with levels reaching 40% of the total dry weight. The alginat form in general is sodium alginat, a water soluble alginat salt. The purpose of this research is to know the quality of alginat include alginat rendamen, water content, ash content, and viscosity. Conventional extraction methods from brown algae into sodium alginat produces the highest yield percentage of 32.42%, resulting from the extraction for 7 hours at 60 ° C. The lowest average yield percentage resulted in 5 hours extraction process of 2.78%, the average water content of 20.37 - 23.30%, the mean ash content of 22.28 - 34.87%, and the viscosity ranged between 18, 0 - 19.8 Cp.